Early Paleozoic high-temperature metamorphism of garnet amphibolite in the Longyou area, Cathaysia Block of South China: P–T path and tectonic implications. (15th June 2021) - Qian, Jiahui; Yin, Changqing; Zhang, Jian; Jin, Xin
Highlights: Longyou garnet amphibolite experienced high-temperature metamorphism, with the Tmax stage at 10 ± 0.9 kbar/840 ± 10 °C. Modal proportions of garnet and plagioclase are closely related to the bulk-rock compositions. The early Paleozoic metamorphism in the Cathaysia Block can be connected to an intraplate orogenic setting. Abstract: Garnet amphibolite can provide crucial information on tectonic processes. Recent progresses on garnet amphibolite in the Longyou area of the Cathaysia Block, South China have attracted geologists' wide concerns and discussions about the regional metamorphic history and geodynamic setting. The Longyou garnet amphibolite shows a prominent porphyroblastic texture involving garnet (~40 vol%), hornblende, clinopyroxene, quartz and ilmenite, with minor plagioclase (<5 vol%), sphene, rutile, pyrite and apatite. Garnet presents as aggregations with double-/multi-nuclear structure and has embayed rims surrounded by quartz and plagioclase. Clinopyroxene is partially replaced by late hornblende and plagioclase. A clockwise high-temperature P–T evolution involving four stages has been determined. The generalized prograde stage shows increases of P–T conditions. The Pmax and Tmax stages lie in P–T conditions of 13 ± 0.6 kbar/808 ± 13 °C and 10 ± 0.9 kbar/840 ± 10 °C, reflecting apparent thermal gradients of ~17 °C/km and 22–23 °C/km, respectively. Both stages match medium-pressure facies series metamorphism. The late retrograde stage shows decompression and cooling. A P–XMg [=Mg/(Mg + Fe) in mole] pseudosection drawn at T = 840 °C suggests that low bulk-rock XMg contents (=0.29–0.33) in the Longyou garnet amphibolite are responsible for the high content of garnet in the rock. A P–M(Na2 O) pseudosection at T = 840 °C reveals that the low content of plagioclase in the rock is caused by low bulk-rock Na2 O contents (=0.44–1.18 mol.%). The integrated P–T–t data from the Cathaysia Block indicate that the early Paleozoic metamorphism can be connected to an intraplate orogenic setting.